STUDIES ON THE LEUKOCYTOSIS AND LYMPHOCYTOSIS INDUCED BY BORDETELLA PERTUSSIS : I. RADIOAUTOGRAPHIC ANALYSIS OF THE CIRCULATING CELLS IN MICE UNDERGOING PERTUSSIS-INDUCED HYPERLEUKOCYTOSIS - Morse, Stephen I. (The Rockefeller University Press, 1967)
By the use of radioautographic techniques it was shown that the lymphocytosis induced by Bordetella pertussis in mice was not caused by an increased production of lymphocytes but was primarily due to the entry into the circulation of mature cells from tissue pools. The accompanying polymorphonuclear leukocytosis was due to both proliferation of myeloid elements and entry of mature cells from tissue reserves, with the former the predominant mechanism.